Is vaccine hesitation related to sociodemographic variables and personality factors? - Pereira, Wanderson Arão do Nascimento; Novais, Adriana de Andrade; Sá, Lucas Guimarães Cardoso de (Interação em Psicologia, 2025)
The objective of this study was to investigate the relationships between vaccine hesitancy and sociodemographic variables and personality factors. The sample consisted of 340 people aged between 18 and 72 years (M = 29.79, SD = 11.19), 65.19% of whom were women. First, a scale was developed to measure vaccine hesitancy; this scale included three factors: confidence in the efficacy of vaccines, fear of negative vaccine reactions and influence of information on vaccine hesitancy. Vaccine hesitancy was compared between different groups, and the influences of sociodemographic variables and five major personality factors on vaccine hesitancy were verified. The results indicated greater vaccine hesitancy in men, people with less education, people with more conservative beliefs and people with a less left-leaning political alignment. Among the personality factors, greater agreeableness, conscientiousness and neuroticism were associated with greater confidence in vaccines. In conclusion, vaccine hesitancy is related to specific sociodemographic variables and personality factors. Promoting the dissemination of correct information about vaccines is necessary to reduce the level of vaccine refusal in people with more characteristics of hesitancy.